HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI PUSKESMAS KALUMATA - Suci Irwanti; Andi Sakurawati; Wahyunita Do Toka (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus transmitted by aedes aegypti mosquitoes. Dengue disease can cause no symptoms so that flu-like symptoms are severe. It is estimated that 3.9 billion people are at risk of contracting dengue virus with 70% of global cases in the Asian region. Clean and healthy behavior is a combination of several behaviors implemented by the community from the results of knowledge in the field of health so that it can become a healthy society. This study aims to determine the relationship between clean and healthy living behavior with the incidence of Dengue Hemorrhagic Fever (DHF) at the Kalumata Health Center in 2022. Observational analytical research with survey methods conducted by distributing questionnaires and interviews to respondents directly with a cross sectional approach. The data obtained were 30 samples and analyzed using the Chi-Square test. Total 30 respondents, there were 20 respondents whose diagnosis status was DHF and 10 respondents were not DHF. 33.3% of respondents were aged around 17-25 years, and 83% were women. Of the 7 variables studied, there are 3 related variables, namely the Habit of Closing the Landfill (p-value = 0.045), the Habit of Burying Used Goods (p-value = 0.007), and the Provision of Abate Powder (p-value = 0.045). while for unrelated variables, namely the habit of draining landfill (p-value = 1,000), installing wire gauze (p-value = 0.705), hanging clothes in the house (p-value = 1,000) and using mosquito repellent (p-value = 0.690). Related variables are the habit of closing the landfill, the habit of burying used goods and giving abate powder. as for unrelated variables, namely the habit of draining landfills, installing wire gauze, hanging clothes in the house and using mosquito repellent.